Quantum Performance Analysis of an EMCCD-based X-ray Detector Using Photon Transfer Technique - Qu, Bin (2010)
The low electronic noise, high resolution, and good temporal performance of electron-multiplying CCDs (EMCCDs) are ideally suited for applications traditionally served by x-ray image intensifiers. In order to improve an expandable clinical detector’s field-of-view and have full control of the system performance, we have successfully built a solid-state x-ray detector. The photon transfer technique was used to quantify the EMCCD quantum performance in terms of sensitivity (or camera gain constant, K), read noise (RN), full-well capacity (FW), and dynamic range (DR). Measured results show the system maintains a K of 11.3 ± 0.9 e(−)/DN at unit gain, with a read noise of 71.5±6.0 e(−)rms at gain 1, which decreases proportionally with higher gains. The full well capacity was measured to be 31.3±2.7 ke(−), providing a dynamic range of 52.8±0.7 dB using the chip manufacturer specified clocking scheme. Similar performance was measured with other commercial camera systems. The manufacturer data sheet indicates a dynamic range of 66 dB is plausible with improved read noise and full well capacity. Different clocking schemes are under investigation to assess their impact on improving performance towards idealized values. EMCCD driver clock voltage levels were adjusted individually to check the influence on quantum performance. The clocks work to transfer charge from the image area to readout amplifier through the storage area, horizontal and multiplication registers. Results indicate that the clock that contributes to lateral overflow drain bias is essential to the system performance in terms of dynamic range and full well capacity. The serial register clocks used for transporting charge stored in the pixels of the memory lines to the output amplifier had the largest effect on RN, while others had less of an impact. Initial adjustment of these clocks resulted in a variability of 16% in the performance of dynamic range, 38% in read noise and 56% in full well capacity. Quantifying the quantum performance provides valuable insight into overall performance and enables optimal adjustment of the clocking scheme. Further improvements are expected.